2002
DOI: 10.1002/pola.10436
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyphosphonates containing pendant chloromethyl groups by the polyaddition of bis(oxetane)s with phosphonic dichlorides

Abstract: The polyaddition of 4,4′‐bis[(3‐ethyl‐3‐oxetanyl)methoxy]biphenyl (4,4′‐BEOBP) and phenylphosphonic dichloride (PPDC) with quaternary onium salts as catalysts proceeded under mild reaction conditions to afford a polymer containing phosphorous atoms in its main chain. A polyphosphonate with a high number‐average molecular weight (10,300) was obtained by the reaction of 4,4′‐BEOBP and PPDC in the presence of tetraphenylphosphonium chloride (TPPC) in o‐dichlorobenzene at 130 °C for 24 h. The structure of the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…24,25 The resulting cured materials are expected to have high hydrophobicity because of their structures without any pendant hydroxy groups. From consideration of these reaction systems, we examined the reaction of oxetanes with aprotic reagents such as acyl chloride, 51,52 thioester, 16 phosphonyl chloride, 53 silyl chloride, 54 and chloroformate 55 (Scheme 3).…”
Section: Kinetics Of the Addition Reaction Of Oxetanes With Protonic mentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 The resulting cured materials are expected to have high hydrophobicity because of their structures without any pendant hydroxy groups. From consideration of these reaction systems, we examined the reaction of oxetanes with aprotic reagents such as acyl chloride, 51,52 thioester, 16 phosphonyl chloride, 53 silyl chloride, 54 and chloroformate 55 (Scheme 3).…”
Section: Kinetics Of the Addition Reaction Of Oxetanes With Protonic mentioning
confidence: 99%
“…Polyadditions of bis(oxetane)s with aprotic reagents such as carboxyl dichloride, 53,54,72 silyl dichloride, 41 phosphonyl dichloride, 53 bischloroformate, 55 and active diesters 73 were carried out using quaternary onium salts as catalysts at 90 8C to afford the corresponding polymers with pendant chloromethyl groups in high yields (Scheme 10).…”
Section: The Polyaddition Reaction Of Bis(oxetane)s With Aprotic Reagmentioning
confidence: 99%
“…6 Since more than 15 years ago, my research group have studied the development of new ring-opening addition reaction of oxetane and succeeded in finding new reactions of oxetanes such as ringopening addition reactions with acyl chlorides, 7 phosphonyl chlorides, 8 silyl chloride, 9 active esters, 7 carboxylic acids, 10 phenols, 11,12 and thiols 13 using appropriate quaternary onium salts or crown ether complexes as catalysts. These reactions can be applied practically to the polyadditions of bis(oxetane)s with above reagents such as diacyl chlorides, [14][15][16][17] phosphonyl dichlorides, 8 active diesters, 18,19 dicarboxylic acids, 10 bisphenols, 11,12 and dithiols 13 to afford corresponding polymers with high molecular weights. Recently, we also found that an anionic ring-opening polymerization of 2-(hydroxymethyl)oxetanes produced corresponding hyperbranched poly(ether)s containing one terminal oxetanyl groups and many pendant primary hydroxy groups using the complex of potassium t-buthoxide with crown ether as a catalyst system, [20][21][22] and an anionic ring-opening alternating copolymerization 23 of oxetanes with cyclic carboxylic anhydrides using certain quaternary onium salts as catalysts.…”
mentioning
confidence: 99%
“…From these scientific backgrounds, the authors examined to develop new organic reactions of oxetane compounds, and succeeded to develop certain new addition reactions of oxetane compounds with acyl chloride, 7 silyl chloride, 8 phosphonyl chloride, 9 phenol, 10 thiol, 11 carboxylic acid, 12 and active ester 13 using certain quaternary onium salts as catalysts, a novel anionic ring-opening polymerization 2-hydroxymethyl oxetanes 14 using potassium tert-butoxide/18-crown-6 as a catalyst, and an anionic ring-opening alternating copolymerization of oxetane with carboxylic anhydride 15 using quaternary onium salts as catalysts. All these reactions proceeded smoothly under suitable reaction conditions to give the corresponding adducts and polymers in satisfactory yields.…”
mentioning
confidence: 99%